Issues of definition the applicable law to an arbitration agreement under the law of the Republic of Kazakhstan - Suleimenov , M.; Ilyasova, K.; Duisenova, A. (International Journal of Psychosocial Rehabilitation, 2020)
The article reveals the topical issues of definition the applicable law to an arbitration agreement based on the legislation of the Republic of Kazakhstan.